Recent update on immunopathogenesis of psoriasis - Seema Chhabra; Sunil Dogra; Keshav Sharma; Smriti K Raychaudhuri; Siba P Raychaudhuri (Wolters Kluwer Medknow Publications, 2022)
Psoriasis is a chronic disabling complex inflammatory disorder prevalent worldwide with environmental and genetic components that involve predominantly skin in addition to nails and joints associated with various systemic comorbidities having periods of exacerbations and remissions. Psoriasis is characterized by hyper-proliferation as well as abnormal differentiation of epidermal keratinocytes and lymphocyte infiltration (mainly T cells) with resultant inflammatory cytokines and chemokines. Immunological and genetic studies over the last decade have identified genetic susceptibility risk alleles, molecular, cellular and immunological mechanisms involved in immunopathogenesis of psoriasis. The current disease model emphasizes the role of aberrant Th1 and Th17 responses regulated by a complex network of different cytokines, including TNF-α, IL-17 and IL-23; signal transduction pathways downstream to the cytokine receptors; and various activated transcription factors, including NF-κB, interferon regulatory factors and signal transducer and activator of transcriptions. Cytokines targeting biologics (IL-17, IL-23 and TNFα) therapies have revolutionized the management of severe skin disease having beneficial effects on joints and systemic inflammation of psoriasis as well. Further better understanding of immunopathogenesis of psoriasis will pave way for precision medicine based on specific immunopathogenic targets in a given phenotype of disease. Complex interplay of psoriasis with associated comorbidities is also a future area of research for overall better patient management and to improve their quality of life.